Cirsium paludigenum and C. zhejiangense (Asteraceae) are synonymous with C. sieboldii and C. yezoense - Jin, Zi-Chao; Chen, You-Sheng (Phytotaxa, 2022)
Based on observations on both herbarium specimens (including type materials) and living plants in their type localities, we demonstrate that Cirsium paludigenum and C. zhejiangense, two taxa recently described both from Zhejiang province of China, are indistinguishable from C. sieboldii and C. yezoense, two species with their type localities from Japan. We therefore reduce C. paludigenum to the synonymy of C. sieboldii, and C. zhejiangense to the synonymy of C. yezoense. The distribution area of both C. sieboldii and C. yezoense are widely expanded in China.